2017
DOI: 10.1093/neuonc/nox187
|View full text |Cite
|
Sign up to set email alerts
|

The elderly left behind—changes in survival trends of primary central nervous system lymphoma over the past 4 decades

Abstract: The poor outcome seen in the particularly vulnerable elderly patient population highlights the need for clinical trials targeting the elderly in hopes of improving treatment strategies and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
155
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(168 citation statements)
references
References 24 publications
(26 reference statements)
10
155
1
2
Order By: Relevance
“…Rather, the median OS reached 8.4 years, increasing remarkably when compared with previous reports . This substantiated the results reported by some specialized centers, as well as those from large national databases, indicating significant improvement in survival of PCNSL over past decades. The generalized improvement in patient outcomes may be attributed to several key reasons, such as the use of autologous stem cell transplant as consolidation therapy, availability of neutrophil growth factors and improved supportive care to bolster the administration of high‐dose MTX as well as multi‐agent chemotherapy, and prevalent use of recent‐generation imaging modalities, namely improved MRI and PET/CT scanners, allowing for accurate staging (eg, elimination of patients with non‐CNS involvement who may have previously been misdiagnosed with PCNSL).…”
Section: Discussionsupporting
confidence: 88%
“…Rather, the median OS reached 8.4 years, increasing remarkably when compared with previous reports . This substantiated the results reported by some specialized centers, as well as those from large national databases, indicating significant improvement in survival of PCNSL over past decades. The generalized improvement in patient outcomes may be attributed to several key reasons, such as the use of autologous stem cell transplant as consolidation therapy, availability of neutrophil growth factors and improved supportive care to bolster the administration of high‐dose MTX as well as multi‐agent chemotherapy, and prevalent use of recent‐generation imaging modalities, namely improved MRI and PET/CT scanners, allowing for accurate staging (eg, elimination of patients with non‐CNS involvement who may have previously been misdiagnosed with PCNSL).…”
Section: Discussionsupporting
confidence: 88%
“…This probably reflects the effect of salvage therapy (such as WBRT) that prolongs survival beyond progression regardless of its negative impact on quality of life. Notably, outcomes of published treatment series do not reflect the “real-life” experience where median OS of the elderly remained in the range of 6–7 months [1, 19]. However, HD-MTX is relatively safe treatment for PCNSL patients regardless of age [23], and even patients aged 80 years or more can tolerate the HD-MTX regimen (such as MPV) [12].…”
Section: Diagnosis and Treatment Of Elderly Patients With Pcnslmentioning
confidence: 99%
“…A recent study revealed that the incidence of PCNSL increased from 0.1 per 100,000 in the 1970s to 0.4 per 100,000 in the 1980s, correlating with an increase in the diagnosis of patients ≥70 years [1]. The incidence in elderly patients aged 70–79 years is 4.32 compared to 0.08 in the 3rd decade of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management of primary central nervous system (CNS) lymphoma (PCNSL) in patients aged ≥70 years represents a significant problem (Welch et al , ; Roth & Hoang‐Xuan, ; Mendez et al , ). While older PCNSL patients generally can tolerate and benefit from high‐dose methotrexate‐based induction, whole brain irradiation consolidation is not favoured because of excessive neurotoxicity.…”
Section: Characteristics Of Elderly Pcnsl Patients Who Received Low‐dmentioning
confidence: 99%